ANALYSIS OF CORPORATE SUSTAINABILITY PRACTICE AND IMPACTS TO CORPORATE VALUES IN MALAYSIA: DATA VISUALIZATION APPROACH - Christopher Jerry Thomas; Jasman Tuyon; Hylmee Matahir; Samir Dixit (International Journal of Accounting, Finance and Business, 2020)
In response to the United Nations sustainable development goals agenda, companiesuses sustainability reporting as a tool to meet stakeholders’ expectation and promotingaccountability which are essential for achieving sustainable competitive advantage andcreating corporate values through sustainability. In recent years, there is a growing body ofsustainability practice and reporting globally, but the nature and extent in Malaysia have notbeen sufficiently explored leaving the impacts of sustainability practice to corporate valuesremain puzzle. This study aims to provide a comprehensive analysis of corporate sustainabilitypractice of FTSE4Good Bursa Malaysia index components through the following analysis.First, review of corporate sustainability policy development. Second, analyse corporatesustainability reporting practice by public listed companies using data visualization tools thatprovide an accessible way to see and understand trends, outliers, and patterns based of ESGscores in relations to firm financial performance proxies. This research would provide insightsinto this new sustainable corporate finance practice, yet very promising in enhancing firmvalues, therefore, have important implications for corporate and portfolio managers.